2014
DOI: 10.1136/bjophthalmol-2014-304959
|View full text |Cite
|
Sign up to set email alerts
|

The role of social deprivation in severe neovascular age-related macular degeneration: Table 1

Abstract: The late presentation and under-representation of patients with greater social deprivation is a serious concern. Our study strongly suggests that this vulnerable group is encountering barriers in accessing treatment in nAMD, and that these occur prior to entry into the Hospital Eye Service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…These include lack of time, lack of knowledge or skills, poor access to evidence, and inefficient care pathways [1619]. In the setting of AMD, barriers such as socioeconomic disadvantage, cost, workforce supply, compliance and adherence issues have been postulated to exist [5, 20]. The current study aimed to explore the perspectives of eyecare professionals (optometrists, ophthalmologists) on AMD care in Australia, with a view to identify and describe some of the possible reasons for under or over detection and inappropriate management.…”
Section: Introductionmentioning
confidence: 99%
“…These include lack of time, lack of knowledge or skills, poor access to evidence, and inefficient care pathways [1619]. In the setting of AMD, barriers such as socioeconomic disadvantage, cost, workforce supply, compliance and adherence issues have been postulated to exist [5, 20]. The current study aimed to explore the perspectives of eyecare professionals (optometrists, ophthalmologists) on AMD care in Australia, with a view to identify and describe some of the possible reasons for under or over detection and inappropriate management.…”
Section: Introductionmentioning
confidence: 99%
“…Data concerning the relationship between SES and VA at presentation of nAMD are scarce. Patients from lower socio‐economic backgrounds had worse VA at first presentation in a study conducted in Birmingham (UK) on 120 patients suggesting that this vulnerable group may have encountered barriers in accessing treatment in nAMD . A study on 240 patients in Scotland presenting between July 2004 and June 2005 found that SES was not associated with VA at presentation of nAMD .…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to many factors including the severity of the neovascular lesion, older age and delayed presentation. A lower socio‐economic status (SES) has been associated with low VA at presentation of nAMD, but this has not been a consistent finding …”
Section: Introductionmentioning
confidence: 99%
“…In this study there was no difference in delivery of treatment between the two groups, however, it should be noted this may be because in the UK anti-VEGF drug treatment for AMD is government funded. 227 In a 2012 Polish study on 201 patients receiving anti-VEGF as a treatment for nAMD compared patients living in urban and rural settings. No difference was noted between these two groups with regard to access to treatment, defined as either time to clinic or time to treatment.…”
Section: Studies From North Americamentioning
confidence: 99%